Legal Protection Of Intellectual Property Rights Owned By Mojorangagung Village - Wiwin Yulianingsih; Sutrisno; Yana Indawati; Hervina Puspitosari; Mas Anienda Tien F (CV. AFDIFAL MAJU BERKAH, 2022)
The development of the digital world is so rapid and has penetrated the business sector, making companies compete with each other to find candidates for digital marketers to support their business. Therefore, it is not surprising that digital marketers are now a separate profession. In addition to thriving digital marketing services are also run by independent agencies. BUMDes must take part in the development of this digital world, considering that BUMDes also run businesses that require a market as a buyer or target market. So that existing developments need to be followed, digital marketing methods must be mastered, because the world is rushing towards the digital era. BUMDes must be aware of digital marketing. Because in this all-digital era, marketing through digital media is very important, and the market has gradually shifted to digital media. Someone will search for a product by just clicking through the search page on Google, or when someone wants to look for village tourism visits, then he will also search on Google or social media.